An investigation into teachers’ occupational well-being and education leadership during the COVID-19 pandemic - Duong, Anh Chien; Nguyen, Hong Nhung; Tran, Anh; Trinh, Thong Minh (Frontiers in Education, 2023)
Due to the COVID-19 pandemic, teachers must adjust rapidly to continue providing effective education. Faced with change, teachers have a more demanding working environment, which has raised national and worldwide concerns about their occupational well-being during the COVID-19 pandemic. Adapting to change and sustaining teachers' professional well-being are essential, but teachers' wellbeing in the pandemic is also crucial. This study contributes to the literature by using questionnaires and semi-structured interviews. It seeks to explore in-service teachers' occupational well-being in Hanoi, Vietnam, and their beliefs about school leaders' efforts to improve teachers' well-being during the COVID-19 pandemic. Convenience sampling was used to collect questionnaire data from 103 inservice teachers and lecturers in Hanoi, Vietnam, in 2021-2022, and eight participants were chosen for interviews via purposive sampling. This study found that, overall, participants had a moderate level of occupational well-being. They also received support from school leaders on professional development, flexibility, and well-being activities during the COVID-19 pandemic. This study's results help teachers comprehend their personal occupational well-being and enhance institutional awareness. The study also illustrates how education stakeholders may promote teachers' occupational well-being during this vital time. The findings have ramifications for teachers and principals.